Strikes, wars and revolutions in international perspective : strike waves in the late nineteenth and early twentieth centuries - Haimson, Leopold; Tilly, Charles (Cambridge : Cambridge University Press, 1989)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: Internationale Arbeidsconferentie; stakingen; sociale vraagstukken; arbeidsconflicten; Europa